2014
DOI: 10.1016/j.neurobiolaging.2014.02.010
|View full text |Cite
|
Sign up to set email alerts
|

High-fat diet-induced memory impairment in triple-transgenic Alzheimer's disease (3xTgAD) mice is independent of changes in amyloid and tau pathology

Abstract: Obesity and consumption of a high-fat diet are known to increase the risk of Alzheimer's disease (AD). Diets high in fat also increase disease neuropathology and/or cognitive deficits in AD mouse models. However, the effect of a high-fat diet on both the neuropathology and memory impairments in the triple-transgenic mouse model of AD (3xTgAD) is unknown. Therefore, groups of 2-month-old male 3xTgAD and control (non-Tg) mice were maintained on a high-fat or control diet and memory was assessed at the age of 3–4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

26
167
2
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 198 publications
(196 citation statements)
references
References 54 publications
(37 reference statements)
26
167
2
1
Order By: Relevance
“…Although the evaluation of HCD effects on cognitive and behavioral functions must be important as same as pathological changes, we did not analyze those, because old PS19 mice showed motor symptoms (paralysis). Recently, Knight et al (2014) reported that high-fat diet induced memory impairment without enhanced amyloid or tau pathology in 3xTgAD mice (APP S we, PS1 M146 , TAU P301L ). This indicates that obesity itself might affect the cognitive functions without enhanced AD pathological changes.…”
Section: Discussionmentioning
confidence: 99%
“…Although the evaluation of HCD effects on cognitive and behavioral functions must be important as same as pathological changes, we did not analyze those, because old PS19 mice showed motor symptoms (paralysis). Recently, Knight et al (2014) reported that high-fat diet induced memory impairment without enhanced amyloid or tau pathology in 3xTgAD mice (APP S we, PS1 M146 , TAU P301L ). This indicates that obesity itself might affect the cognitive functions without enhanced AD pathological changes.…”
Section: Discussionmentioning
confidence: 99%
“…Epidemiological survey shows that consumption of too much saturated fat is a high risk factor of AD (Eskelinen et al, 2008;Laitinen et al, 2006). High fat diet could induce CNS A accumulation and memory impairment in mice (Knight et al, 2014;Refolo et al, 2001). More and more evidences suggest that low calorie diet can delay the progress of brain aging (Martin et al, 2006).…”
Section: Diet Gut Microbiota and Admentioning
confidence: 99%
“…HFD was shown to have rapid and long-lasting negative effects on memory in model mice with and without Alzheimer's disease (34). The open field test is a classic experimental method for behavioral evaluation, including locomotor activity and exploratory behavior, and the electric maze test is used to assess learning and memory.…”
Section: Discussionmentioning
confidence: 99%